2021
DOI: 10.31533/pubvet.v15n10a943.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Secuestro corneal felino: Reporte de caso

Abstract: O sequestro corneal é uma patologia estabelecida a partir da necrose do estroma que leva ao desenvolvimento de uma pigmentação difusa ou bem demarcada, com variações entre preto e dourado. Essa doença é grave e afeta os olhos de felinos de diferentes idades, sendo que o tratamento precoce e apropriado evita complicações como dor e a perfuração ocular. O prognóstico é frequentemente favorável, porém há riscos de recorrência caso o tratamento não seja realizado adequadamente. O objetivo desse trabalho é relatar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Severe intravascular haemolysis caused by the destructive potential of MF could have attributed to the anemia in accordance with the reports of Diptelonema reconditum infected dogs(Hashem & Badawy, 2007). Similarly,Madril et al (2020) reported that anaemia in diro lariosis could be due to the mechanical trauma of the red blood cells and vascular walls caused by the movement of the parasites. Anaemia of in ammation is characterized by mild to moderate non-regenerative anemia and neutrophilic leukocytosis that occurs due to multiple downstream effects of released cytokines, which shift granulocytic cell production in bone marrow, decreasing erythroid production(Grimes and Fry, 2015).…”
mentioning
confidence: 95%
“…Severe intravascular haemolysis caused by the destructive potential of MF could have attributed to the anemia in accordance with the reports of Diptelonema reconditum infected dogs(Hashem & Badawy, 2007). Similarly,Madril et al (2020) reported that anaemia in diro lariosis could be due to the mechanical trauma of the red blood cells and vascular walls caused by the movement of the parasites. Anaemia of in ammation is characterized by mild to moderate non-regenerative anemia and neutrophilic leukocytosis that occurs due to multiple downstream effects of released cytokines, which shift granulocytic cell production in bone marrow, decreasing erythroid production(Grimes and Fry, 2015).…”
mentioning
confidence: 95%